Analisis Efisiensi Dan Efektivitas Anggaran Pendapatan Dan Belanja Desa (Apbdes) Pada Kantor Balai Desa Pagendisan, Kec. Winong, Kab. Pati - Tri Hartininngsih; Lis Widowati; Amy Cahyawati3 (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2025)
Analysis of efficiency and effectiveness in the management of the Village Revenue and Expenditure Budget (APBDes) is useful for ensuring that village financial resources are used optimally. Management of the Village Revenue and Expenditure Budget (APBDes) in Pagendisan Village, Winong District, Pati Regency has indicated that it is less effective and less efficient in its allocation. This study aims to determine the financial performance of the Pagendisan Village government in managing the Village Revenue and Expenditure Budget (APBDes) based on the level of efficiency and effectiveness ratios in 2021-2023. The method used in this study is quantitative descriptive using data in the form of numbers to describe, research, and explain it. The data sources used in this study are primary data and secondary data. Data collection techniques in this study are observation, interviews. The results of this study, namely based on the efficiency ratio, show that the financial performance of the Pagendisan Village government from 2021-2023 is less efficient in realizing expenditures with total income. Meanwhile, based on the effectiveness ratio, it shows that the financial performance of the Pagendisan Village government from 2021-2023 is very effective in achieving the set revenue targets